PERAN LOKASI USAHA DAN LITERASI DIGITAL TERHADAP PENINGKATAN PENDAPATAN UMKM SEBAGAI PENDORONG PERTUMBUHAN EKONOMI - Ridaul Innayah; Yosia Dian Purnama Windrayadi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2026)
The achievement of sustainable national economic growth cannot be separated from the contributions of various parties, UMKM as part of the contributor to national income figures. UMKM income itself is influenced by business location and digital literacy. The chosen business location determines the bankruptcy or success of a business (Tinneke et al., 2020). Digital literacy has a direct and indirect influence on UMKM performance. However, in reality, many UMKM still do not have adequate business locations and do not have sufficient digital literacy, and there are differences in research results regarding the effect of business location on UMKM performance. This study is interested in reviewing how: a) the influence of business location in increasing UMKM income, b) the influence of digital literacy in increasing UMKM income, and c) the influence of business location and digital literacy together in increasing UMKM income. The population of this study was UMKM in Tuban Regency using Accidental Sampling, and obtained 101 respondents. The main instrument for data collection was a closed questionnaire, supplemented by interviews and observations. According to the results of the hypothesis test, the business location has a sig. 0.109, digital literacy level sig. 0.503, and the sig. value of both independent variables in the F test is 0.250. Thus, it is concluded: a) Business location has no influence on efforts to increase UMKM income, b) Digital literacy has no influence on increasing UMKM income, and c) Business location and digital literacy together have no influence on increasing UMKM income.Â